THE EDUCATIONAL ISSUE OF DEVELOPING AESTHETIC EDUCATION IN PRESCHOOL CHILDREN THROUGH FOLK APPLIED DECORATIVE ART - Khasanov Kholboy Khasanovich; Abdulazizova Mubina Bori qizi (Bright Mind Publishing, 2025)
The article considers visual activity as one of the key means of aesthetic education. Therefore, in explaining tasks, it is necessary to choose vivid and precise words to describe objects and phenomena. When such an approach is applied, inviting children to draw pictures or to model objects from clay and plasticine not only evokes strong emotional excitement in their hearts but also fosters creativity and individuality. The paper highlights educational problems and specific pedagogical aspects related to integrating such activities into preschool educational programs and effectively explaining them during classes.
Keywords: Aesthetic education, folk applied decorative art, national values, applied art objects, joypush, kirpech, zardevor, bo‘g‘joma, headscarves.